Assessment of the area of influence of San José-Sabanilla-La Campiña public transportation trunk corridor: Applying the transit oriented development methodology - Segura Segura, Daniela (2025)
The lack of territorial planning in the Great Metropolitan Area (GMA) has led to urban growth so dispersed and disordered (Rodríguez, 2017). In addition to this, the inefficient public transport system has caused a dependency on the private vehicle, which generates large costs to the country in economic, social and environmental terms (PEN, 2015). Thus, the main challenge for GAM is to plan land use in conjunction with an efficient transport system. The main proposals for urban development are aimed at joint planning between transport and land use, as well as favouring pedestrian movements (Cardozo, Gutiérrez, & García, 2010). One way of evaluating if the city is planned in terms of mobility is though the TOD (Transit Oriented Development) Standard methodology, which is a tool for assessing whether urban development plans and products adhere to the principles of urban mobility (ITDP, 2017). This article presents the results of a research (Segura, 2019) in which the Standard TOD methodology was applied (ITDP, 2017) to evaluate the area of influence of five bus stops in a section of the San José-Sabanilla-La Campiña mass transit trunk, which is part of the GAM mass transit modernization project. Based on the score obtained, it was determined that the study area was not planned in terms of mobility and were identify some interventions that could significantly improve it. In addition, some recommendations are presented that should be implemented in the planning of the corridor, such as densifying the area, investing in public space and mixed land uses, so that, once the GAM mass transit modernization project is implemented, users will be encouraged to use this system.